IMPLEMENTASI PENGUATAN PENDIDIKAN KARAKTER DI SEKOLAH DASAR QUR’ANI AL-IKHLASH RAPPANG KABUPATEN SIDENRENG RAPPANG - Jumiati Lanta; Lababa Riana (JRPD (Jurnal Riset Pendidikan Dasar), 2019)
This research aim to  description: 1) how profile elementary school Qur’ani Al- Ikhlas Rappang (Sidenreg Rappang Regency), and 2) reinforcement of  Implementation education character at elementary school Qur’ani Al- Ikhlas Rappang (Sidenreng Rappang Regency). This research it was descriptive kualitative research  through case study. The data resources were; head master, teachers, Parents, and pupil of elemntary school Qur’ani Al-Ikhlas Rappang. Technique collecting data by using observation, intervew and documentation. Data analysis by using Milles Huberman technique was covered; data reduction, provided data, verification data. To make validitatioan data, the research was  used  triangulasi sources and triangulasi method. The research result showed that was; 1) elementary school Qur’ani Al- Ikhlash Rappang was one of the basic  Islamic private elemntary  school, located in Rappang, Distric pancarijang, Sidenreng Rappang regency, south sulawasi , Indonesia. This school was builded in 2014 as collabaration Wahdaislamiyah Sidenreng Rappang Regency with inhabitants, and parents of the students. This institute was overation by fullday school system and have point of view “ bertauhid dan berprestasi”; 2) Implementation education character elemntary school Qur’ani Al-Ikhlash Rappang implemnted through culture and school system as well as; best attitude, education, makes good condition, good suggest, good communication, 9K concep (kerapian, kebersihan, ketertiban, kesopanan, keindahan, kerindangan, kedisiplinan, keimanan, dan ketaqwaan). The aplication of education charakter  through cleaning around school with self awarness. Everyday, teachers showed attitude to keep clean around the school, as well as students have become accustomed to cleaned their class  without command.